A systematic review on healthcare financing in Singapore - R., Mohammad Farhan; U. Z., Hussaini; J., Saifulsyahira; A. M., Rosliza (Community Health Society Malaysia, 2016)
Background: Healthcare financing has been on the global agenda for many countries to elevate the health status of the citizens at the same time aim for a lean and sustainable health system. Singapore in particular has demonstrated progressive leaps in health care financing through various reforms.